Collaboration and More-Than-Human Interactions in Conservation Research About National Historic Waterways in Ontario - Beaudoin, Christine (Université d'Ottawa / University of Ottawa, 2022)
Relationships between humans and the environment are messy and complex. This thesis makes sense of this complexity by using relational approaches to bridge social-ecological systems research with insights from the more-than-human social sciences and humanities. I focus on the case of environmental governance and conservation research in two of Ontario's National Historic Waterways: the Rideau Canal and the Trent-Severn Waterway. I analyze knowledge maps of factors that influence the environment of the waterways and the perception of relationships between humans and non-humans in the context of research. Through social-ecological network analysis, it was revealed different that groups conceptualize the Rideau Canal differently, but that all groups overemphasized social factors when identifying components that influence the environment. Knowledge maps, representing participants' mental models of the Rideau Canal, are used to generate narratives to inform policy and engagement strategies. Social-ecological network analysis was also used to make visible the different types of relationships between humans and non-humans in the context of conservation research. This unveiled a paradox of conservation. Attempts to produce evidence to conserve non-human populations and habitats are anchored in tense encounters, and sometimes procedures that are harmful for the individuals targeted by the research. I mobilize relational approaches and concepts from the social sciences to propose practical and theoretical insights and pathways for conservation research to become more-than-human. Such work necessitates the explicit recognition of the contributions of non-humans in research processes.
Keywords: Collaboration; Non-humans; Friction; Relational sociology; Social-ecological networks; Rideau Canal; Trent-Severn Waterway